The hardness of five acrylic artificial teeth brands marketed in Bandung city - Dziab, Hasna; Hasratiningsih, Zulia; Kurnikasari, Erna (Universitas Padjadjaran, 2008)
The acrylic artificial teeth are still among the most frequently used artificial teeth. Some commercial brands marketed in Bandung claim that their products have met the existing standards. However, those brands do not give any mechanical property data, including data on hardness. The ADA specification standard no. 15 requires a hardness of minimum 15.00 KHN for acrylic artificial teeth. The aim of this study is to find out which acrylic artificial teeth actually have a standardized hardness value. The study is an analytical descriptive study, which is performed on 5 brands of acrylic artificial teeth marketed in Bandung. From each brand, 4 teeth were sampled and receive 10 indentation spots on the upper and lower surfaces. It is concluded that the five acrylic artificial teeth brands have met the ADA specification standard no. 15 and there are differences in hardness values among the five brands.